2020
DOI: 10.1038/s41467-020-16393-4
|View full text |Cite
|
Sign up to set email alerts
|

CX-5461 activates the DNA damage response and demonstrates therapeutic efficacy in high-grade serous ovarian cancer

Abstract: Acquired resistance to PARP inhibitors (PARPi) is a major challenge for the clinical management of high grade serous ovarian cancer (HGSOC). Here, we demonstrate CX-5461, the first-in-class inhibitor of RNA polymerase I transcription of ribosomal RNA genes (rDNA), induces replication stress and activates the DNA damage response. CX-5461 cooperates with PARPi in exacerbating replication stress and enhances therapeutic efficacy against homologous recombination (HR) DNA repair-deficient HGSOC-patient-derived xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(162 citation statements)
references
References 53 publications
(79 reference statements)
10
151
1
Order By: Relevance
“…The recent demonstration in HCT-116 cells, that CX-5461 induces a prominent intracellular DNA damage through inhibition of topoisomerase II activity, indicates that DDR could be the major mechanism of CRC cell death induction [182]. Similarly, in p53 mutant HT-29 and COLO-205 CRC cell lines, CX-5461 treatment is inducing apoptosis [179], but possibly through a mechanism that triggers replication stress and DDR activation, as reported in high-grade serous ovarian cancer [183]. CX-5461 is in phase I/II clinical trials for hematological cancers [184], but further investigations are necessary to understand the crosstalk between ribosome biogenesis inhibition and DDR activation induced by CX-5461 treatment of CRC cells.…”
Section: Targeting Ribosome Rna Synthesis In Colorectal Cancermentioning
confidence: 90%
“…The recent demonstration in HCT-116 cells, that CX-5461 induces a prominent intracellular DNA damage through inhibition of topoisomerase II activity, indicates that DDR could be the major mechanism of CRC cell death induction [182]. Similarly, in p53 mutant HT-29 and COLO-205 CRC cell lines, CX-5461 treatment is inducing apoptosis [179], but possibly through a mechanism that triggers replication stress and DDR activation, as reported in high-grade serous ovarian cancer [183]. CX-5461 is in phase I/II clinical trials for hematological cancers [184], but further investigations are necessary to understand the crosstalk between ribosome biogenesis inhibition and DDR activation induced by CX-5461 treatment of CRC cells.…”
Section: Targeting Ribosome Rna Synthesis In Colorectal Cancermentioning
confidence: 90%
“…Interestingly, some recent studies suggested that targeting nucleolar proteins/processes in combination with PARP inhibitor treatment may be beneficial for the treatment of some cancers, e.g., by overcoming PARP inhibitor resistance mechanisms. Thus, in a recent study CX-5461 was demonstrated to induce replication stress and activate the DNA damage response in high-grade serous ovarian cancer (HGSOC) cells [173]. CX-5461 showed significant therapeutic benefit as a single agent in HGSOC-patient-derived xenografts with reduced sensitivity to PARP inhibitors by overcoming replication fork protection, which is a well-known PARP inhibitor resistance mechanism.…”
Section: Implications For Cancer Biologymentioning
confidence: 99%
“…159 The ATR inhibitor BAY 1895344 has demonstrated some antitumor activity in a single agent phase 1 study in solid tumors 160 ; this agent could be considered for combination with 177 Lu-PSMA-617. The RNA polymerase I inhibitor CX-5461 has also demonstrated synergy with talazoparib in preclinical models of ovarian cancer 161 breakthrough treatments for many cancers including melanoma, lung cancer and others because of the marked and durable responses and unprecedented survival benefit. 163,164 However these agents have had limited activity in prostate cancer, [165][166][167][168][169][170][171]…”
Section: Psma Rnt Rational Combinationsmentioning
confidence: 99%